2‐Hydroxy‐1, 4‐naphthoquinone [Lawsone] integrated rare‐earth hybrid materials as biocompatible UV/IR filter agents. Issue 1 (27th January 2023) - Narayanan, Sheemol V.; Kumar, Muthusundar; Gnanaraj, Valan R.; Rajan, Sruthi C.; Selvaraj, Viji; Ananthakumar, Solaiappan
Abstract: UV filter agents are essential ingredients in cosmetics and fabrics for rendering the property of protection from harmful UV radiation. The focus of this research was on the development of biocompatible hybrid UV/IR filter agents through sol–gel processing of nano‐sized lanthanum titanate, zirconate, and phosphate‐based rare‐earth materials. 2‐Hydroxy‐1, 4‐naphthoquinone (Lawsone) is an ideal candidate, owing to its biocompatibility, for treating the sol of the rare‐earth systems to produce inorganic‐organic hybrids with classical orange shades. The rare‐earth hybrids were characterized by X‐Ray diffraction, dynamic light scattering, fourier transform infrared spectroscopy, scanning electron microscopy, UV‐Vis, photo‐luminescence, and Near Infrared (NIR) spectroscopy. The results of characterization indicated that the hybrids offer >90% of NIR reflectance in the wavelength region from 700 to 1100 nm. They also exhibited excellent shielding in UV‐A and UV‐B regions, thus qualifying them as cool colors with useful optical as well as heat management characteristics. The sun protection factor calculated by optical density measurements showed that the synthesized hybrids have potential applications as UV filter agents in sunscreen lotions. The cell viability analyzed by the MTT (4, 5‐dimethylthiazol‐2‐yl)−2, 5‐diphenyltetrazolium bromide) assay affirmed the biocompatibility of the hybrids as none of the systems was found cytotoxic. This study was devoted to exploring the beneficial properties of rare‐earth‐based hybrid systems in pharmacological applications. Abstract : Nontoxic, biocompatible UV filter agents by integrating the chemical and physical functionality of the rare‐earths and organic Lawsone with excellent sun protection value.